1991
DOI: 10.1104/pp.97.3.894
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 2-Carboxyarabinitol 1-Phosphatase

Abstract: The regulation of 2-carboxyarabinitol 1-phosphatase (CA 1-Pase) by phosphorylated effectors was studied with enzyme purified from tobacco (Nicotiana tabacum) leaves. CA 1-Pase activity was most stimulated by fructose 1,6-bisphosphate, exhibiting an Ao.5 value of 1.9 millimolar and a 10-fold enhancement of catalysis. With nbulose-1,5-bisphosphate, the AO.5 was 0.6 millimolar, and maximal stimulation of activity was 5.3-fold. Among the monophosphates, 3-phosphoglycerate and phosphoglycolate were more potent posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
5
25
1
Order By: Relevance
“…Previous studies have shown that purified leaf and recombinant activase are extremely heat-labile if incubated in the absence of ATP (Robinson and Portis, 1989;Holbrook et al, 1991;Eckardt and Portis, 1997). Our results corroborated these findings, because we observed inactivation of both forms upon exposure to relatively moderate temperatures (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that purified leaf and recombinant activase are extremely heat-labile if incubated in the absence of ATP (Robinson and Portis, 1989;Holbrook et al, 1991;Eckardt and Portis, 1997). Our results corroborated these findings, because we observed inactivation of both forms upon exposure to relatively moderate temperatures (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…DCMU did not affect the rate of [14C]CAlP accumulation in the dark, but did greatly reduce the rate of its degradation in the light, a result comparable to a previous observation made using leaf discs (18). Although CAlP phosphatase activity in vitro is inhibited about 50% by Pi (7), the lack of any observed mannose effect on CAlP metabolism (Table II) indicates that Pi may not normally have any regulatory function, contrary to a previous suggestion (7,15). The inhibition of CAlP accumulation in the dark by DTT and NaF were quite unexpected (Table II).…”
Section: Discussioncontrasting
confidence: 55%
“…Evidence was presented that heat stress perturbed the structural properties of activase. In support of this hypothesis, the activity of isolated activase has been shown to be extremely sensitive to high temperature (Robinson and Portis, 1989;Holbrook et al, 1991;Crafts-Brandner et al, 1997;. Crafts-Brandner et al (1997) presented evidence that high temperature inhibited activase by disrupting subunit interactions.…”
mentioning
confidence: 77%
“…Isolated activase is extremely heat labile (Robinson and Portis, 1989;Holbrook et al, 1991;Crafts-Brandner et al, 1997;, and the different polypeptide forms of activase differ in their sensitivity to inactivation by high temperature (Crafts-Brandner et al, 1997). The basis of thermal sensitivity appears to be disruption of subunit interactions that are necessary for activity (CraftsBrandner et al, 1997).…”
Section: Discussionmentioning
confidence: 99%